PEMANFAATAN GAWAI ANDROID UNTUK PENJUALAN GERABAH - Sri Wening; Maria Atik Sunarti Ekowati; Kristyana Dananti (CV. ALIM'SPUBLISHING, 2023)
The Bayat community is a community that has skills in making pottery crafts. Selling pottery crafts is one of the uses of individual creativity and skills and talents possessed by the Pagerjurang Bayat Klaten community which can be used to create prosperity and employment opportunities through the creativity and inventiveness of individual communities. The potential that exists not only requires capital, energy and funds for manufacturing, but Bayat village pottery entrepreneurs need to change their marketing strategy by using modern technology in the form of using Android devices in building their marketing strategy. This Community Service aims to motivate pottery entrepreneurs to form creative ways of thinking and productive behavior in developing marketing through Android devices. The Community Service Method uses qualitative and quantitative methods as a strategy for achieving goals. And as a result of community service activities, pottery craftsmen are able to implement marketing strategies using Android devices, so that sales turnover targets are achieved